2020
DOI: 10.5194/acp-20-14253-2020
|View full text |Cite
|
Sign up to set email alerts
|

New particle formation at urban and high-altitude remote sites in the south-eastern Iberian Peninsula

Abstract: Abstract. A substantial fraction of the atmospheric aerosols originates from secondary new particle formation (NPF), where atmospheric vapours are transformed into particles that subsequently grow to larger sizes, affecting human health and the climate. In this study, we investigate aerosol size distributions at two stations located close to each other (∼ 20 km) but at different altitudes: urban (UGR; 680 m a.s.l., metres above sea level) and high-altitude remote (SNS; 2500 m a.s.l.) sites, both in the area of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 72 publications
5
17
0
Order By: Relevance
“…The following diameters were used in the inversion: 1.1, 1.3, 1.5, and 2.4 nm. The choice of the inversion method was made after a comprehensive comparison between the kernel method and the expectation and minimization (EM) method (Cai et al, 2018;Chan et al, 2020). Additional details about the comparability of the two methods and the utilized inversion parameters are presented in Sect.…”
Section: Data Handlingmentioning
confidence: 99%
“…The following diameters were used in the inversion: 1.1, 1.3, 1.5, and 2.4 nm. The choice of the inversion method was made after a comprehensive comparison between the kernel method and the expectation and minimization (EM) method (Cai et al, 2018;Chan et al, 2020). Additional details about the comparability of the two methods and the utilized inversion parameters are presented in Sect.…”
Section: Data Handlingmentioning
confidence: 99%
“…N total calculated in this study is also consistent with those observed in other urban and remote areas with Mediterranean-type climate. In Granada, Spain the total number concentration for particles below 500 nm was 8500 cm −3 [30], which is almost equal to those at Thissio, and the lower levels calculated at other background Mediterranean environments such as Ispra, Italy [31], were comparable to Finokalia. The higher N total in Amman corresponds well with those recorded at Barcelona, Spain in a year-long measurement campaign [32].…”
Section: Particle Number Size Distributionsmentioning
confidence: 57%
“…Significant J O( 1 D) values of (in s −1 ) were observed during the day (from about 07:00 to 17:00 LT) with a maximum value of 2×10 −5 s −1 at noon and symmetrically distributed before and after noon. The average calculated H 2 SO 4 concentration during particle formation periods (10:00-12:00 LT) was about 1.4 × 10 7 cm −3 , about an order higher than that (about 7-12 × 10 6 cm −3 ) in a mountain region in Germany (Wu et al, 2013) and close to that (about 2-5 × 10 7 cm −3 ) in a rural region of Sichuan in China (Chen et al, 2014). Considering a relative error of about 20 %, the growth rate contributed by condensation of gaseous H 2 SO 4 was about 0.61-1.09 nm h −1 or about 7.6 %-13.6 % of the observed growth rates for 3-10 nm particles.…”
Section: Measurement-based Npf Simulationsmentioning
confidence: 70%